IMMUNOMODULATORY ACTIVITY OF EXTRACT OF KESUM (Polygonum minus Huds.) LEAF AND EXTRACT OF PACAR AIR Impatiens balsamina Linn.) HERB AND ITS THERAPEUTIC EFFECT IN ANIMAL MODEL OF RHEUMATOID ARTHRITIS âAN AUTOIMMUNE DISEASE - I H, Hariyanto
Rheumatoid arthritis is an inflammatory reaction caused by deposited of immune complexes in the joints. Traditionally, kesum (Polygonum minus Huds.) leaf and pacar air (Impatiens balsamina Linn.) herb have been used to treat inflammation and rheumatism. This is allegedly related to its immunomodulatory activity. The objective of this study was to investigate the activity of kesum leaf and pacar air herb as an immunomodulator agents and its therapeutic effects in animal model of rheumatoid arthritis. The active compounds of kesum leaf and pacar air herb were extracted using ethanol 96% by maceration method. Immunomodulatory activity of both plant extracts was determined by carbon clearance test and the index of immune organs. Anti-arthritis activity of the test extracts was determined in rat adjuvant-induced arthritis (AIA) model. The rats were injected with CFA intraplantarly to induce arthritic animal model. The anti-arthritic effect of the extracts was determined by measurement of the paw volume, joint edema, daily body weight and TNF-?levels determined using ELISA technique. Results showed that kesum leaves extract at dose of 175 and 320 mg/kg bw and pacar air herbs at dose of 250 and 500 mg/kg bw have immunosuppressant activity with phagocytic index < 1. Those extracts also showed immune organs index which were significantly (p<0.05) lower than control group. The rats were successfully induced arthritic with 0.25 mL of CFA. The administration of extract for 14 days started from day 8 th during chronic arthritic condition significantly (p<0.05) reduced the total volume of paw and joint edema while no effect on body weight. The highest percentage of inhibition was caused by high dose of pacar air extract (500 mg/kg bw) with percentage of inhibition for paw and joint edema were 29.6% and 24.9%, respectively. The TNF-?levels in all doses of extract groups decreased however only both doses of pacar air extract showed significantly lower (p<0.05) compared to that of control. Based on the results obtained, kesum leaf and pacar air herb ethanol extracts have immunosuppressive activity and able to reduce arthritis symptoms in rat adjuvant induce arthritis model. Thereby, both extracts are potential to be further developed as an alternative for treating rheumatoid arthritis.